Bone marrow fibrosis in childhood acute lymphoblastic leukaemia. - Wallis, J P (1989)
Bone marrow trephine biopsy specimens were obtained at diagnosis from 63 of 76 consecutively presenting children with acute lymphoblastic leukaemia (ALL). The association between marrow fibrosis and presenting features, including immunophenotype, was analysed. Reticulin was increased in 45 of 56 cases in which blasts expressed B lineage markers, but in only one of seven with T-ALL. A weak association was also found between marrow fibrosis and splenomegaly in those with common ALL. Marrow fibrosis is apparently associated with some examples of ALL of B cell lineage, but precisely which subtypes and whether the phenomenon is clinically important remain to be determined.